The oceanic cycles of the transition metals and their isotopes - Vance,D; Archer,C; Little,SH; Kobberich,M; de,Souza GF (Acta Geochimica, 2017)
The stable isotope systems of the transition metals potentially provide constraints on the current and past operation of the biological pump, and on the state of ocean redox in Earth history. Here we focus on two exemplar metals, nickel (Ni) and zinc (Zn). The oceanic dissolved pool of both elements is isotopically heavier than the known inputs, implying an output with light isotope compositions. The modern oceanic cycle of both these elements is dominated by biological uptake into photosynthesised organic matter and output to sediment. It is increasingly clear, however, that such uptake is associated with only very minor isotope fractionation. We suggest that the isotopic balance is instead closed by the sequestration of light isotopes to sulphide in anoxic and organic-rich sediments, so that it is ocean chemistry that controls these isotope systems, and suggesting a different but equally interesting array of questions in Earth history that can be addressed with these systems.